2012
DOI: 10.3102/0013189x12459883
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Skills and School Success in Young Children Experiencing Homelessness

Abstract: The authors examined the role of executive function (EF) skills as a predictor of kindergarten or first-grade adjustment in 138 children living in shelters for homeless families. During the summer, children completed a battery of six EF tasks and three IQ measures. Teachers later rated children’s school adjustment in five domains of achievement and social conduct. Confirmatory factor analysis supported the construct validity of EF as distinct from the general factor in IQ tests. The differential predictive val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 45 publications
(96 reference statements)
10
126
3
2
Order By: Relevance
“…The assessment of EF skills is therefore considered important given that EFs have been found to be an important factor for school success (Masten et al, 2012). Some EFs require little emotional control, while others call for a great deal of emotional control, as highlighted by Masten et al Preschool children seem to be especially sensitive to assimilating ways of regulating their own emotions and behaviour (Center on the Developing Child at Harvard University, 2011).…”
Section: Selfregulation Planningmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessment of EF skills is therefore considered important given that EFs have been found to be an important factor for school success (Masten et al, 2012). Some EFs require little emotional control, while others call for a great deal of emotional control, as highlighted by Masten et al Preschool children seem to be especially sensitive to assimilating ways of regulating their own emotions and behaviour (Center on the Developing Child at Harvard University, 2011).…”
Section: Selfregulation Planningmentioning
confidence: 99%
“…Executive functions develop with age and experience (Masten et al, 2012;Cartwright, 2012). It is suggested that brain areas related to EFs develop in parallel to reading acquisition (Cartwright, 2012).…”
Section: Wm Is An 'Executive Function'mentioning
confidence: 99%
See 3 more Smart Citations